Promotion mechanism of high-involvement human resource management practices to employees’ bootlegging: A moderated mediation model - Jia, Jianfeng; Liu, Zhi; Liu, Weipeng; Hu, Jieli (Frontiers in Psychology, 2023)
Bootlegging is a frontier topic in micro-innovation literature. Existing research on the external environment-antecedents of employees’ bootlegging focuses mainly on organizational innovation management practices and leadership. The relationship between human resource management and employees’ bootlegging is still unclear. Thus, we follow the stimuli-organism-response model and use psychological ownership theory to examine a moderated mediation model with psychological ownership as a mediator and Chinese traditionality as a moderator to interpret how and when high-involvement human resource management practices influence employees’ bootlegging. We administered three-wave time-lagged surveys to 251 employees and used SEM analysis to test the hypotheses. The results show that high-involvement human resource management practices is positively related to employees’ psychological ownership. Whereas psychological ownership, in turn, positively related to bootlegging. Meanwhile, employees’ psychological ownership plays a significant mediating role between high-involvement human resource management practices and employees’ bootlegging. The results further showed that employees’ Chinese traditionality weakens the influence of psychological ownership on bootlegging and the mediating effect of employees’ psychological ownership between high-involvement human resource management practices and employees’ bootlegging. This study makes several contributions to the bootlegging antecedent mechanism research and inspires enterprises in innovation and talent management.